On positional connections of central punctors space - Žiaukienė, S. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: С. П. Жяукене. Связности в пространстве центральных пункторов S. Žiaukienė. Centrinių punktorių erdvės sąryšiai